Political consumerism: An integrative review - Juliana de Oliveira Becheri; Lauriene Teixeira Santos; Joel Yutaka Sugano; Paulo Henrique Montagnana Vicente Leme (Contextus, 2022)
Consumers are gradually becoming more conscious of the strength of their consumption, expressing discontent and opinions and demanding improvements in organizations. Due to the extensive theoretical background, this article aims to compile research about political consumption through an integrative review on WOS and Scopus. At the end of the methodological procedures, 36 articles were obtained and analyzed with the content analysis technique. The results show that personal influences and motivations for political consumption are based on sociodemographic situation, political ideology, and internet use. This framework synthesized the phases of political consumption, the main actions, and the main actors involved.